Implementation of the Integrative Holistic Program in Early Childhood Education - Sagita Aqlia Nurfahma; Khaerani Saputri Imran; Farida Rohayani; Muammar Qadafi (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
This study aims to understand the implementation of the five holistic integrative program services and the factors that hinder and support the implementation of the holistic integrative program in Early Childhood Education institutions. The research method used is qualitative with a descriptive approach, with data obtained through observation, interviews, and documentation techniques. The results show that the implementation of the five holistic integrative program services has been applied by conducting learning activities that can develop all aspects of child development, parenting activities, posyandu activities, and collaborating with several stakeholders such as health centers (puskesmas), DP2KBP3A, and the civil registration office (dinas dukcapil) to provide services and ensure the well-being of the students.